Perubahan Perilaku Manusia Dalam Perspektif Al-Qur’an: Formulasi Pencegahan HIV/Aids - Nur Winda; Andi Rezal Juhari; Andi Nida’ul Hasanah (TAFASIR: Journal of Quranic Studies, 2023)
HIV/AIDS is no longer a rare disease, because the level of infection is widespread and a concern, which is one of the factors causing it is promiscuity. Therefore, Allah regulates his servants in the realm of association or behavior in order to avoid harm. This paper uses the thematic tafsir research method (maudu'i) which discusses the verse of the Qur'an related to changes in behavior to avoid HIV/AIDS, and is supported by arguments and facts that can be accounted for, as stated in QS. Ar-Rad verse 11 and QS Al-Isra verse 32. The implication of this research is that by applying health promotion strategies in the form of advocacy, partnership, and community empowerment, the community, especially adolescents who are vulnerable to falling into promiscuity, can be educated through socialization and procurement of pocket books as an indication of HIV/AIDS prevention.Keywords : Behavior change, Qur’an, HIV/AIDS